ANALYSIS OF A LOW PROTEIN DIET (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Recommendation of a low-protein diet for patients with chronic kidney disease in the pre-dialysis period had a clear positive effect in terms of slowing down the progression, improving the metabolic parameters and nutritional status of patients. In the daily diet, protein is 0,6-0,7 g per 1 kg of body weight of patients, the main "suppliers" of energy are fats and carbohydrates, which fully satisfy the daily energy needs of patients.